Studi Knowledge, Skill, dan Efikasi Diri Terhadap Kinerja Mahasiswa dalam Berwirausaha - Muis Murtadho; Roby Kurniawan Budhi; Risma Andrarini (UNUSA Press, 2017)
The objective of this research is to examine the effect of knowledge, skills and selfefficacy on the performance of student entrepreneurship. The research method is quantitative research. The object of this research is the students of Widya Kartika University who already have business as many as 45 students. The results of this research is the variable of knowledge does not affect the performance of student entrepreneur significantly, but the variable of skill and self-efficacy effect on the performance of student entrepreneurship significantly. From the results of the analysis, it can be seen that knowledge cannot be relied upon to improve the performance of entrepreneurship, on the contrary, good skills and high confidence of students greatly affect the performance of student entrepreneurship.